Influence of graphene oxide and carbon nanotubes on the fatigue properties of silica/styrene-butadiene rubber composites under uniaxial and multiaxial cyclic loading. (February 2020) - Xu, Zongchao; Jerrams, Stephen; Guo, Hao; Zhou, Yanfen; Jiang, Liang; Gao, Yangyang; Zhang, Liqun; Liu, Li; Wen, Shipeng
Graphical abstract: Highlights: The combination of CNT (or GO) and SiO2 improved the fatigue properties. GO-SiO2 /SBR exhibited the lowest crack growth rate under uniaxial cyclic loading. GO-SiO2 /SBR exhibited the longest fatigue lives under multiaxial cyclic loading. σmax can be used as a reliable fatigue life predictor for SBR composites. Abstract: The influence of equivalent replacement of silica (SiO2 ) by carbon nanotubes (CNT) or graphene oxide (GO) on the microstructure, mechanical and fatigue behaviors of SiO2 /styrene-butadiene rubber (SBR) composites was investigated. Results showed that the synergistic effect between CNT (or GO) and SiO2 was beneficial for the filler network and improved the mechanical properties of SBR composites. Furthermore, the introduction of CNT (or GO) led to low crack growth rates and the crack propagation tips were easy to deflection. Under multiaxial fatigue conditions, the maximum engineering stress was determined to be a reliable fatigue life predictor for SBR composites.